Chronic Pain and Psychological Distress Among Undocumented Latinx Immigrants in the USA - Garcini, Luz M. (J Gen Intern Med, 2021)
BACKGROUND: Undocumented immigration is often accompanied by multiple and complex stressors, which over time may increase the risk for chronic pain. OBJECTIVE: This study aimed to identify the prevalence of chronic pain and its association with psychological distress among undocumented Latinx immigrants in the USA. DESIGN/PARTICIPANTS: We used respondent-driven sampling to collect and analyze data from clinical interviews with 254 undocumented Latinx immigrants, enabling inference to a population of 22,000. MAIN MEASURES: Chronic pain was assessed using the World Health Organization Composite International Diagnostic Interview (CIDI) Chronic Conditions Module. For all analyses, inferential statistics accounted for design effects and sample weights to produce weighted estimates. We conducted logistic regression analyses to assess the association between chronic pain and psychological distress after controlling for age, years in the USA, and history of trauma. RESULTS: A total of 28% of undocumented Latinx immigrants reported having chronic pain, and 20% of those had clinically significant psychological distress. Significant differences in the prevalence of chronic pain were reported across age groups, years in the USA, and trauma history. After controlling for relevant covariates, chronic pain was significantly associated with psychological distress (OR = 1.06, 95% CI [1.02, 1.09]), age (OR = 1.05, 95% CI [1.02; 1.09]), and history of trauma (OR = 1.10 per additional traumatic event, 95% CI [1.02; 1.19]; C-statistic = 0.79). CONCLUSION: Among undocumented Latinx immigrants, chronic pain is significantly associated with psychological distress, older age, and trauma history. Given that undocumented immigrants have restricted access to healthcare and are at high risk for chronic pain, developing alternatives to facilitate access to chronic pain interventions and risk-reduction prevention are needed.